Navajo Nation Snowpack Variability from 1985‐2014 and Implications for Water Resources Management. (April 2018) - Tsinnajinnie, Lani M.; Gutzler, David S.; John, Jason
Abstract: In the arid Southwest, snowpack in mountains plays an essential role in supplying surface water resources. Water managers from the Navajo Nation monitor snowpack at nine snow survey stations located in the Chuska Mountains and Defiance Plateau in northern Arizona and New Mexico. We characterize these snowpack data for the period 1985‐2014 and evaluate the efficacy of snowpack data collection efforts. Peak snow water equivalent occurs in early to mid‐March depending on elevation. Variability in snowpack levels correlates highly among all sites (r > 0.64), but higher elevation sites in the Chuska Mountains correlate more strongly with one another compared to lower elevation sites and vice versa. Northern sites also correlate well with each other. A principal component analysis is used to create a weighted average time series of year‐to‐year peak snowpack variability. The first principal component showed no trend in increasing or decreasing Navajo Nation snowpack. Results from this research will provide the Navajo Nation Department of Water Resources information to help determine if any snow survey sites in the Chuska Mountains are redundant and can be discontinued to save time and money, while still providing snowpack information needed by the Navajo Nation. This summary of snowpack patterns, variability, and trends in the Chuska Mountains and Defiance Plateau will help the Navajo Nation to understand how snowpack and water resources respond to climate change and climate variability.